The Contribution of ‘Urf to the Reform of Islamic Inheritance Law in Indonesia - Ismail, Ismail; Busyro, Busyro; Nofiardi, Nofiardi; Wadi, Fajrul; Alwana, Hanif Aidhil (Al-Risalah, 2022)
This library research explains the position of ‘urf as the basis for reforming Islamic law and its contribution to the renewal of inheritance law in Indonesia, using the content analysis method. The result showed that ‘urf is of higher importance in the renewal of Islamic law and plays a very important role in reforming the inheritance law in Indonesia. Several KHI book II provisions were based on ‘urf, including the inheritance of adopted children and adoptive parents, żawul arḥām, radd, walad, joint property, and substitute heirs. Among the several forms of ‘urf that have been recognized as Islamic law, ‘urf of joint property comes from the rich culture and traditions of native Indonesia. Therefore, it has made a valuable contribution to the renewal of Islamic law in Indonesia.